# SOLUTION: Multiply: (5&#8730;[2] + 3)(&#8730;[2] – 2&#8730;[3])

Algebra ->  Algebra  -> Polynomials-and-rational-expressions -> SOLUTION: Multiply: (5&#8730;[2] + 3)(&#8730;[2] – 2&#8730;[3])       Log On

 Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations! Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help!

 Algebra: Polynomials, rational expressions and equations Solvers Lessons Answers archive Quiz In Depth

 Click here to see ALL problems on Polynomials-and-rational-expressions Question 111589: Multiply: (5√[2] + 3)(√[2] – 2√[3]) Found 2 solutions by stanbon, MathLover1:Answer by stanbon(57953)   (Show Source): You can put this solution on YOUR website!Multiply: (5√[2] + 3)(√[2] – 2√[3]) ------------- Use FOIL: F: 5sqrt(2) * sqrt(2) = 10 O: 5sqrt(2) * -2sqrt(3) = -10sqrt(6) I: 3 * sqrt(2) = 3sqrt(2) L: 3*-2sqrt(3) = -6sqrt(3) ----------------- Combine to get: 10(1-sqrt(6))+3(sqrt2-2sqrt(3) ============== Comment: Are you sure that "3" in the problem you posted is not really "sqrt(3)"?? =========== Cheers, Stan H. Answer by MathLover1(6806)   (Show Source): You can put this solution on YOUR website! Since , and (in your case numbers ) then we have: ………… Note that is not necessarily true when dealing with numbers that are